2023
DOI: 10.3389/fmars.2023.1073322
|View full text |Cite
|
Sign up to set email alerts
|

Increased histone H3 acetylation inhibit the inflammatory response and activate the serum immunity of Pearl oyster Pinctada fucata martensii

Abstract: To produce cultured pearls, a mantle graft with a nucleus is transplanted into a host pearl oyster, this process is called “transplantation”. The immune response of pearl oyster after transplantation is a major factor that leads to nucleus rejection and death. Butyrate is a histone deacetylase (HDAC) inhibitor which can inhibit the deacetylation process of histones and effectively reduce the inflammatory response. To clarify the function of histone acetylation in immune response after transplantation, butyrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Recent research in vertebrates and invertebrates has shown that histone acetylation primarily occurs on four histone proteins (H2A, H2B, H3, and H4), with H3 and H4 exhibiting the highest levels of acetylation [ 127 , 128 ]. Notably, acetylation of histone H3 can modulate ATP-dependent chromatin remodeling, thereby contributing to the inflammatory response, while histone H4 acetylation influences chromatin transcription and replication [ 129 , 130 , 131 ]. Concerning shrimps, all four histone proteins capable of acetylation have been identified, revealing their involvement in possible regulatory mechanisms [ 132 ].…”
Section: Types Of Epigenetic Modificationsmentioning
confidence: 99%
“…Recent research in vertebrates and invertebrates has shown that histone acetylation primarily occurs on four histone proteins (H2A, H2B, H3, and H4), with H3 and H4 exhibiting the highest levels of acetylation [ 127 , 128 ]. Notably, acetylation of histone H3 can modulate ATP-dependent chromatin remodeling, thereby contributing to the inflammatory response, while histone H4 acetylation influences chromatin transcription and replication [ 129 , 130 , 131 ]. Concerning shrimps, all four histone proteins capable of acetylation have been identified, revealing their involvement in possible regulatory mechanisms [ 132 ].…”
Section: Types Of Epigenetic Modificationsmentioning
confidence: 99%
“…Some of the most toxic elements that are spread on sandy beaches are heavy metals [17], Polycyclic Aromatic Hydrocarbons (PAHs) [18], and pesticides [19]. These compounds are ubiquitous in the environment and have potentially adverse effects on organisms and public health owing to their toxic, carcinogenic, and mutagenic properties [20].…”
Section: Introductionmentioning
confidence: 99%